Coaching, counseling & mentoring : how to choose & use the right technique to boost employee performance - Stone, Florence M. (American Management Association, 2007)
This updated and revised second edition includes useful scripts for talking to employees about sensitive issues, and new material on topics including working with off-site employees, what to say when an employee denies a problem exists, whether or not to coach temps and part-timers, how to draw the line between the mentoring and supervisory role, and what to do when counseling fails.